2011
DOI: 10.3934/dcds.2011.29.193
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and abstract computability: Computing invariant measures

Abstract: We consider the question of computing invariant measures from an abstract point of view. We work in a general framework (computable metric spaces, computable measures and functions) where this problem can be posed precisely. We consider invariant measures as fixed points of the transfer operator and give general conditions under which the transfer operator is (sufficiently) computable. In this case, a general result ensures the computability of isolated fixed points and hence invariant measures (in given class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 18 publications
0
57
0
1
Order By: Relevance
“…A metatheorem ( [4], [2]) then allows to remove the non-deter-minism and to obtain a deterministic algorithm. Implicitly, such an approach is exhibited in [24] by Rettinger for computability of Jordan curves, and by Galatolo, Hoyrup and Robas in [8] showing computability results for invariant measures. The present paper constitutes another application of this type.…”
Section: Non-deterministic Type-machinesmentioning
confidence: 99%
“…A metatheorem ( [4], [2]) then allows to remove the non-deter-minism and to obtain a deterministic algorithm. Implicitly, such an approach is exhibited in [24] by Rettinger for computability of Jordan curves, and by Galatolo, Hoyrup and Robas in [8] showing computability results for invariant measures. The present paper constitutes another application of this type.…”
Section: Non-deterministic Type-machinesmentioning
confidence: 99%
“…About the general problem of computing invariant measures, it is worth to remark that some negative result are known. In [9] it is shown that there are examples of computable 2 systems without any computable invariant measure. This shows some subtlety in the general problem of computing the invariant measure up to a given error.…”
Section: Introductionmentioning
confidence: 99%
“…Computable, here means that the dynamics can be approximated at any accuracy by an algorithm, see e.g [9]. for precise definition.…”
mentioning
confidence: 99%
“…The computability of Julia sets has been particularly popular, see, e.g., [18,19,9,3,4,12,11,13,10]. There are several results about the computability of certain specific measures, see [3,20] and the references therein, such as a maximal entropy measure or physical measure, the numerical computation of entropy and dimension for hyperbolic systems, see, e.g., [35] and [36] and the references therein, as well as with the computation of the topological entropy/pressure for one and multi-dimensional shift maps, see, e.g., [29,47,48,28,56,57]. To the best of our knowledge, our attempt is the first to establish computability of an entire entropy spectrum within the space of all invariant measures.…”
mentioning
confidence: 99%